A retrospective analysis of the results of the six Belarusian five-year plans and the tasks for the seventh five-year plan - Kovalev, Mikhail M.; Koroleva, Anna A. (Journal of the Belarusian State University. Economics, 2025)
This article continues the authors’ series on the evolution of the Belarusian economic model and reveals the challenges facing the country’s economy during the seventh five-year plan. A retrospective statistical analysis of the results of each of the six five-year plans allowed us to identify the challenges facing the Belarusian economy and, based on these, formulate priorities for 2026 –2030, which can be used in developing economic policy.